Intermammary pilonidal sinus – A case report - Patel, Digant; Vasava, Manoj; Patel, Jagrut; Shah, Rutul; Patel, Jigar; Yadav, Vivek (Indian Journal of Case Reports, 2020)
Pilonidal sinus is a blind-end tract lined with granulation tissue, which leads to a cystic cavity lined with epithelial tissue. This case report aims to present a case of pilonidal sinus presenting in an unusual location – the intermammary region, in a 16-year-old female patient who presented with complaints of serous discharge mixed with pus intermittently from the intermammary region for 5 months. Although a pilonidal sinus is most commonly seen at the sacrococcygeal region, the presence of one such entity in the intermammary region of a female represents a rare occurrence with very few cases reported worldwide – more so in young females with large, heavy, and pendulous breasts. A proper surgical repair in terms of its excision and closure remains the mainstay in management.